Cross-Context Responses to Novelty in Rural and Urban Small Mammals - Mazza, Valeria; Czyperreck, Inken; Eccard, Jana A.; Dammhahn, Melanie (Frontiers in Ecology and Evolution, 2021)
The Anthropocene is the era of urbanization. The accelerating expansion of cities occurs at the expense of natural reservoirs of biodiversity, and presents animals with challenges for which their evolutionary past might not have prepared them. Cognitive and behavioral adjustments to novelty could promote animals’ persistence under these altered conditions. We investigated the structure of, and covariance between, different aspects of responses to novelty in rural and urban small mammals of two non-commensal rodent species. We ran replicated experiments testing responses to three novelty types (object, food, or space) of 47 individual common voles (Microtus arvalis) and 41 individual striped field mice (Apodemus agrarius). We found partial support for the hypothesis that responses to novelty are structured, clustering i) speed of responses, ii) intensity of responses, and iii) responses to food into separate dimensions. Rural and urban small mammals did not differ in most responses to novelty, suggesting that urban habitats do not reduce neophobia in these species. Further studies investigating whether comparable response patters are found throughout different stages of colonization, and along synurbanization processes of different duration, will help illuminate the dynamics of animals’ cognitive adjustments to urban life.